(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The results of experimental research of variable parameters of Issyk-Kul are presented in this paper. This paper presents the results of field studies and the results of numerical calculations of the changing biogenic parameters of lake Issyk-Kul. The developed mathematical model of the dynamics of the biomass of phytoplankton in built methods for evaluation of chlorophyll content, given its distribution and depth depending on the different cases of light penetration. Based on the processing of satellite images of lake Issyk Kul in different ranges, data on the increase in the area of biogenic materials on the surface of lake Issyk Kul were obtained for the first time.